Assessing soil quality for rehabilitation of salt-affected agroecosystem: A comprehensive review - Basak, Nirmalendu; Rai, Arvind Kumar; Sundha, Parul; Meena, Rameshwar Lal; Bedwal, Sandeep; Yadav, Rajender Kumar; Sharma, Parbodh Chander (Frontiers in Environmental Science, 2022)
One billion hectare of land worldwide is affected by several kinds of salinity and associated problems. The soil quality (SQ) in salt-affected soil (SAS) is impaired because of the presence of excess electrolytes, disproportionate Na and Ca in soil solution and exchange phase, rhythmic changes in the hydrological cycle, decreasing soil organic matter, poor vegetative cover, low soil biological activity, and crop residue return. The sodic and saline¬¬-sodic soils have the potential to provide alkaline reactions and soil physical constraints regulate the soil attributes affecting SQ. Because of high spatial variability and rapid temporal changes selection of simple, robust, low cost, and high throughput master indicators for assessing SQ are very essential for monitoring the aggradation or degradation of SAS. Therefore, screening the master indicators for developing minimum data set for SQ assessment of SAS is an important issue for sustainable management of soil in these agro–ecologies. We captured the SQ indicators for SAS from several ecosystems of different countries and discussed the problems of parameterization for assessing SQ. Improved SQ for optimum soil functioning is the needed for confirming agricultural productivity and food security of the globe. This review describes the causes and drivers for sodification/salinization and mechanism–oriented rehabilitation options such as the application of mineral gypsum, flue-gas-desulfurized gypsum, elemental S, acidify biochar, polymer, salt tolerance mechanisms, and other agro-techniques for improving the quality of SAS. Based on the SQ assessment, a suite of site-specific soil management practices are advocated for the greening of SAS and prosperity.